2011
DOI: 10.1099/vir.0.031955-0
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in nasal polyps in a Chinese population

Abstract: In order to determine the prevalence and genotype distribution of human papillomavirus (HPV) infection in patients with nasal polyps, a total of 204 patients with nasal polyps and 36 healthy controls were recruited for this study. Genomic DNA was extracted from paraffin-embedded tissue sections. HPV DNA genotyping was achieved by a flow-through hybridization and gene-chip method. HPV-positive infection was identified in 82 of 204 (40.2 %) patients, while HPV DNA was not found in healthy controls (P,0.05). Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
5
26
1
Order By: Relevance
“…On the contrary, HPV infection was absent in SNP-WAD patients and in SNP-WoAD patients without a relapsing disease. These results confirm the importance of the methodological approach in the selection of patients for the study of this pathology and support previous results [33], where HPV-11 was observed as the prevalent infection SNP. Interestingly, HPV infection was restricted to epithelial cells, as it is known to be highly tropic for epithelial cells, while no infection sign was evidenced in fibroblast cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, HPV infection was absent in SNP-WAD patients and in SNP-WoAD patients without a relapsing disease. These results confirm the importance of the methodological approach in the selection of patients for the study of this pathology and support previous results [33], where HPV-11 was observed as the prevalent infection SNP. Interestingly, HPV infection was restricted to epithelial cells, as it is known to be highly tropic for epithelial cells, while no infection sign was evidenced in fibroblast cells.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in literature have analyzed the role of HPV infection in SNP, demonstrating different correlation ranges [5, 6, 33]. We hypothesize that these differences may be due to the absence of a preselection of patients according to the presence or absence of allergic diseases that could be a confounder for the results observed.…”
Section: Discussionmentioning
confidence: 86%
“…With the developments in laboratory medicine and the sensitive detection technology available in clinical practice, multiple infections by different HPV genotypes, including HR‐HPV and LR‐HPV, can be easily and accurately identified, making large public health screening for HPV genotyping in a clinic or health center possible. With its very efficient technique for molecular hybridization, flow‐through hybridization has been recognized as an appropriate tool for HPV genotyping . In this study, a newly developed technique that combines flow‐through hybridization and gene chip was used to perform HPV genotyping in women.…”
Section: Discussionmentioning
confidence: 99%
“…Flow-through hybridization is the most efficient method for molecular hybridization [911]. A newly developed biotechnology named HybriMax, combining two advanced techniques, the flow-through hybridization and gene chip, is developeded to be used in clinical practice for the detection and genotyping of 21 different types of HPVs at one test.…”
Section: Discussionmentioning
confidence: 99%
“…However, its main undeniable limitation is that HC-II cannot distinguish between different HPV genotypes definitely [5, 8]. Recently, a new HPV-genotyping method combining two advanced techniques, the flow-through hybridization and gene chip (HybriMax) has been used to detect and genotype HPV, which can distinguish 21 different types of HPV DNA in a single test and diagnose multiple infections [911]. In this study, we have evaluated the efficacy of HybriMax on cervical HPV genotyping through comparison of the results with Hybrid Capture II (HC-II) and in situ hybridization (ISH).…”
Section: Introductionmentioning
confidence: 99%